PEMANFAATAN APLIKASI GAME MATEMATIKA BERBASIS KUIS UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWA KELAS III MADRASAH IBTIDAIYAH - Faizatul Widat; Nur Aliffia Shafillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of the Kahoot quiz-based game application in improving the numeracy skills of grade III A MI Al-Islamiyah students. This research uses a qualitative approach with a qualitative descriptive type. The research subjects consisted of 22 students of class III A and class teachers who were selected purposively. Data collection techniques are carried out through observation, interviews, documentation, and tests, while data analysis uses the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawn. The validity of the data was tested through triangulation of techniques and sources. The results of the study show that the use of Kahoot in mathematics learning is able to create a more interactive and fun learning atmosphere. Students become more enthusiastic, active, and motivated in participating in learning, so their involvement in the learning process increases significantly compared to conventional learning. Elements of the game such as scores and rankings also provide a positive encouragement for students to focus more and strive to achieve the best results. In addition, the use of Kahoot also has an impact on improving students' numeracy skills, especially in solving basic calculation operations such as addition, subtraction, multiplication, and division. Students become faster, more precise, and more confident in answering questions. Thus, it can be concluded that the use of Kahoot makes a positive contribution to improving the learning process and mathematics learning outcomes of students.